Ecrire sous la forme a + b sqrt5 ou a et b sont deux nombres entiers relatifs.

a. ( 6 - 2 sqrt 5 ) + ( sqrt 5 - 3 )

b. ( 1 + sqrt 5 ) (sqrt 5 - 2 )

c. ( 2 + sqrt 5 ) ( 3 - 2 sqrt 5 )

d. ( 2 + 2sqrt5 ) - (1 - 2sqrt5 )

sqrt = racine carre

MERCI! :D

1

Réponses

2014-04-06T20:02:14+02:00
A. ( 6 - 2 sqrt 5 ) + ( sqrt 5 - 3 ) = 3-sqrt 5

b. ( 1 + sqrt 5 ) (sqrt 5 - 2 )  = sqrt 5  -2 + 5 - 2 sqrt 5 = 3 - sqrt 5

c. ( 2 + sqrt 5 ) ( 3 - 2 sqrt 5 ) = 6 -4 sqrt 5 + 3 sqrt 5 - 10 = -4 - sqrt 5

d. ( 2 + 2sqrt5 ) - (1 - 2sqrt5 ) = 1 + 4 sqrt 5

Voila !